The Influence of Spirituality during Pregnancy: The Lights and Shadows - Nusrat Nisar, Syed Zulfiquar Ali Shah, Imran Karim, Urooj, Zubida, Taha Rajar (Pakistan Journal of Medical & Health Sciences, 2024)
In Asia, religion and health have been intertwined for centuries. Many cultures relate pregnancy and childbirth with religion and tradition. Spirituality is vital to nursing and midwifery. It is the part of all nursing and midwifery clients’ and families’ care1. Women pray more for protection, safe delivery, and blessings throughout pregnancy. Some women dread death during caesarian section and others are stigmatized2. It endures, to birth spontaneously; expectant ladies would try all spiritual and conventional techniques. Women pray alone or together. Pregnant ladies pray to build their faith in God and have confidence in a safe delivery3. Women communicate differently depending on their religion. Women can pray with blessed water, threads, recited water and oil. These items can be used once or throughout pregnancy4. The Holy Spirit is supposed to influence users through blessed water and oil. Some women recite scripture during prayers. Religious restrictions for pregnant women vary by group.